(untitled) (Research, Society and Development, 2021)
Aim: In vitro evaluation of the influence of bovine xenogenic biomaterials on stem cells from human exfoliated deciduous teeth (SHEDs). The study was divided into three groups: 1) group C (control), containing only MSCs; 2) group BP, containing MSCs and Bonefill Porous®; 3) group BO, containing MSCs and Bio-Oss®. MSCs were derived from a deciduous tooth from a 7-year-old male donor. An aliquot of cells was subjected to immunophenotyping by flow cytometry. Cell viability (neutral red), cytotoxicity (MTT), and cell proliferation (crystal violet) assays were performed. All groups underwent morphological analysis by light microscopy (LM), and the biomaterial with superior performance was submitted to evaluation by scanning electron microscopy (SEM). Time points of 24, 48, and 72 h of culture were used. All results were evaluated with a significance level of 0.05. Results showed that both biomaterials maintained cell viability and cytotoxicity similar to the control. The BO group showed smaller cell proliferation compared to the other groups. In LM evaluation, the BP group showed more spread and adherent cells than the BO group. In SEM, cells of the BP group showed characteristics of more active cells than those of the control. Bovine xenogenic biomaterials positively influenced SHEDs, while the BP group seemed to present higher potential with SHEDs for future application within in vivo and/or clinical studies.